Avaliação do uso de bagaço de malte em esferas de alginato aplicadas em biorremediação de hidrocarbonetos alifáticos do petróleo - Eichler, Paulo (2022)
Bioremediation of oil spill contamination, through encapsulation of hydrocarbon degrading microorganisms in alginate spheres, is currently an alternative of great interest due to its relatively low cost and lower environmental impact than traditional solutions (chemical and physical). The present work aimed to evaluate the use of Malt Bagasse (MB) as a low-cost source of nutrients, which can be inserted into alginate spheres to assist in the initial growth of microorganisms, without negatively altering the mechanical properties of the spheres. The spheres were produced with 1% (m/m) of sodium alginate, 1% (m/m) of commercial consortium of microorganisms and different compositions of MB. Initial growth of microorganisms, bead characterizations and biodegradation of aliphatic hydrocarbons were evaluated using different compositions of MB in alginate beads. Higher initial growth of microorganisms was observed in the spheres with higher MB composition, however the incorporation of 3% of MB presented a higher elastic modulus (398 kPa). The 40-day bioremediation test showed that, for the aliphatic hydrocarbon fraction from C12 to C27, there is a tendency that higher concentration of MB in the spheres also increases the percentage of bioremediation. The spheres with 5% MB showed the best bioremediation results with an overall average percentage of 75% and average percentages of 81%, 64% and 61% for medium chain hydrocarbons (C12 to C18), long chain hydrocarbons (C19 to C27) and isoprenoids (pristane and phytane), respectively.